Propionate attenuates atherosclerosis by immune-dependent regulation of intestinal cholesterol metabolism. (1st October 2021) - Haghikia, Arash; Zimmermann, Friederike; Schumann, Paul; Jasina, Andrzej; Roessler, Johann; Schmidt, David; Heinze, Philipp; Kaisler, Johannes; Nageswaran, Vanasa; Aigner, Annette; Ceglarek, Uta; Cineus, Roodline; et al.
Abstract: Aims: Atherosclerotic cardiovascular disease (ACVD) is a major cause of mortality and morbidity worldwide, and increased low-density lipoproteins (LDLs) play a critical role in development and progression of atherosclerosis. Here, we examined for the first time gut immunomodulatory effects of the microbiota-derived metabolite propionic acid (PA) on intestinal cholesterol metabolism. Methods and results: Using both human and animal model studies, we demonstrate that treatment with PA reduces blood total and LDL cholesterol levels. In apolipoprotein E −/− ( Apoe −/− ) mice fed a high-fat diet (HFD), PA reduced intestinal cholesterol absorption and aortic atherosclerotic lesion area. Further, PA increased regulatory T-cell numbers and interleukin (IL)-10 levels in the intestinal microenvironment, which in turn suppressed the expression of Niemann-Pick C1-like 1 (Npc1l1), a major intestinal cholesterol transporter. Blockade of IL-10 receptor signalling attenuated the PA-related reduction in total and LDL cholesterol and augmented atherosclerotic lesion severity in the HFD-fed Apoe −/− mice. To translate these preclinical findings to humans, we conducted a randomized, double-blinded, placebo-controlled human study (clinical trial no. NCT03590496). Oral supplementation with 500 mg of PA twice daily over the course of 8 weeks significantly reduced LDL [−15.9 mg/dL (−8.1%) vs. −1.6 mg/dL (−0.5%), P = 0.016], total [−19.6 mg/dL (−7.3%) vs. −5.3 mg/dL (−1.7%), P = 0.014] and non-high-density lipoprotein cholesterol levels [PA vs. placebo: −18.9 mg/dL (−9.1%) vs. −0.6 mg/dL (−0.5%), P = 0.002] in subjects with elevated baseline LDL cholesterol levels. Conclusion: Our findings reveal a novel immune-mediated pathway linking the gut microbiota-derived metabolite PA with intestinal Npc1l1 expression and cholesterol homeostasis. The results highlight the gut immune system as a potential therapeutic target to control dyslipidaemia that may introduce a new avenue for prevention of ACVDs. Graphical Abstract: